The application of the habitats directive in Portugal - Costa, José C. (2007)
A succinct review of the application of the Habitats Directive in Portugal is presented. Since 1971 until 2000 Portugal has defined approximately 8,8% of its territory as national protected areas. With the application of the Habitats Directive nature conservation policies extended to more than 17,4 % of the territory increasing by 98% and the knowledge on vegetation community’s habitats was certainly deepened. Including special protection areas (Birds Directive) the Portuguese territory under one or more conservation status totals 21,5%. Finally, the support given by the Portuguese Phytosociology Association – ALFA in the detailed description of the Directive habitats is divulged, showing the importance, usefulness and efficacy of phytosociologic studies. Applicazione della Direttiva Habitat in Portogallo. Viene presentata una succinta revisione dell’applicazione della Direttiva Habitat in Portogallo. Tra il 1971 e il 2000 il Portogallo ha definito come aree nazionali protette circa l’8,8% del suo territorio. L’applicazione della Direttiva Habitat ha significato un aumento del 98% delle aree sottoposte a protezione legale, raggiungendo il 17,4% circa del territorio e un approfondimento della conoscenza degli habitat delle comunità vegetali. Includendo le zone speciale di protezione (Direttiva Uccelli) si totalizza il 21,5%. Nelle conclusioni si evidenzia il ruolo della Associazione Portoghese di Fitosociologia (ALFA) nella descrizione dettagliata degli habitat della Direttiva, dimostrando l’importanza, l’utilitá e l’efficacia degli studi fitosociologici.